Towards a framework of smart city diplomacy. (March 2018) - Mursitama, T N; Lee, L
Abstract: This article addresses the impact of globalization on the contemporary society, particularly the role of the city that is becoming increasingly important. Three distinct yet intertwine aspects such as decentralization, technology, and para diplomacy become antecedent of competitiveness of the city. A city has more power and authority in creating wealth and prosperity of the society by utilizing technology. The smart city, in addition to the importance of technology as enabler, we argue that possessing the sophisticated technology and apply it towards the matter is not enough. The smart city needs to build smart diplomacy at the sub-national level. In this article, we extend the discussion about smart city by proposing a new framework of smart city diplomacy as one way to integrate information technology, public policy and international relations which will be the main contribution to literature and practice.